Single seedling nursery tray - Wayayok, Aimrun; Zubairu, Usman Bashar; Mohd Soom, Mohd Amin; Mahadi, Mohamad Razif (2013)
The present invention provides a seedling nursery tray for transplanting propagates or plants into field, the seedling nursery tray (10) includes: a) a main tray (20) with plurality of seedling cavities or planting cells (22) disposed therein to enable seedlings grow independently in separated media, wherein the main tray (20) facilitates substantial root disturbance free environment that enables seedling’s roots grow deep; and b) a sliding base (30) slidably introduced to the main tray (20), wherein the sliding base (30) facilitates to serve as a support and/or valve in holding and/or releasing seedlings from the main tray (20) to transplanter for planting into the field.